2002
DOI: 10.1892/0891-6640(2002)016<0669:ipaaid>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability and Absorption in Dogs with Traumatic Injury

Abstract: The objectives of this study were to assess the feasibility of using urinary recovery of sugars to evaluate intestinal permeability and absorption in dogs with traumatic injury and to determine if intestinal permeability and absorption are altered in dogs with traumatic injury. After a 6-hour fast, a sugar solution containing lactulose, rhamnose, 3-O-methyl-D-glucose, and xylose was administered via nasoesophageal tube. Urine was collected and quantitated over the 6-hour study period via closed collection urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The dogs in the previous study were different than humans in that by 72 hours after trauma, the L/R ratios were returning to normal, whereas humans continued to have abnormal L/ R ratios 96 hours after trauma. Poor intestinal blood flow could be responsible for the intestinal mucosal damage in both the study of Streeter et al 18 and our study. However, visceral ischemia is not supported by the study of Van Citters and Franklin, 19 who showed no reduction in splanchnic blood flow in exercising sled dogs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The dogs in the previous study were different than humans in that by 72 hours after trauma, the L/R ratios were returning to normal, whereas humans continued to have abnormal L/ R ratios 96 hours after trauma. Poor intestinal blood flow could be responsible for the intestinal mucosal damage in both the study of Streeter et al 18 and our study. However, visceral ischemia is not supported by the study of Van Citters and Franklin, 19 who showed no reduction in splanchnic blood flow in exercising sled dogs.…”
Section: Discussionsupporting
confidence: 62%
“…A study on dogs with traumatic injury (eg, blunt trauma with fractures, hemothorax, or pneumothorax) found that their L/R ratio was significantly higher at 48 hours after trauma than that of controls. 18 Although mean values were not presented in that study, inspection of the figures shows that control dogs had a mean L/R of approximately 0.06, whereas dogs 48 hours after trauma had a mean L/R of approximately 0.10. The dogs in the previous study were different than humans in that by 72 hours after trauma, the L/R ratios were returning to normal, whereas humans continued to have abnormal L/ R ratios 96 hours after trauma.…”
Section: Discussionmentioning
confidence: 80%
“…51 GI disturbances in critically ill dogs have been poorly documented; however, a recent prospective study documented an increase in GI permeability in dogs with traumatic injury. 74 Additionally, research models have documented diminished canine intestinal motility following sublethal endotoxemia. 75 Clearly, further evaluation of GI function is warranted in critically ill dogs.…”
Section: Gi Dysfunctionmentioning
confidence: 99%